2010
DOI: 10.2139/ssrn.1686109
|View full text |Cite
|
Sign up to set email alerts
|

Study on Dividend Policy: Antecedent and its Impact on Share Price

Abstract: Research BackgroundDividend announcement by a company is a signal to shareholders. Basically, managers and shareholders have different information, where managers have more complete information than shareholders. The shareholders will interpret the increase in dividend payments by the company, as the signal that management has a high cash flow forecast future (Black, 1976). Conversely, the decline in dividend payments interpreted as anticipation manager of the limited cash flow in the future. Lintner (1956) ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Al-hasan et al (2013) told that dividend policy had more influences to the stock price than retained earnings. Furthermore, Murhadi (2008) found that company which shared its dividend to shareholders had more liquid in capital stock market than the company which not shared its dividend to shareholders. Hasnawati (2005) did some research to 259 public companies which were listed in Indonesia Stock Exchange (IDX).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Al-hasan et al (2013) told that dividend policy had more influences to the stock price than retained earnings. Furthermore, Murhadi (2008) found that company which shared its dividend to shareholders had more liquid in capital stock market than the company which not shared its dividend to shareholders. Hasnawati (2005) did some research to 259 public companies which were listed in Indonesia Stock Exchange (IDX).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile independent variables which are internal cash flow, insider ownership, and investment opportunity. Internal cash flow proxied by natural logarithm of net profit of the company after payment of debt and tax (profit after tax) (Murhadi 2010). Insider ownership measured by add manager ownership and commissioner ownership percentage (Murhadi 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Internal cash flow proxied by natural logarithm of net profit of the company after payment of debt and tax (profit after tax) (Murhadi 2010). Insider ownership measured by add manager ownership and commissioner ownership percentage (Murhadi 2010). Investment opportunity measured by comparison between book value of property, plant and equipment (PPE) with book value of total assets (BVA).…”
Section: Methodsmentioning
confidence: 99%
“…Aharony and Swary (1980) after analyzing quarterly Dividend and Earnings Announcements, concluded that dividends and earnings were strong support for the signaling theory. Werner (2018) tested Dividend Signaling Theory in an Indonesian Capital Market using quantitative approach method of path analysis from 1995 to 2005. The study found that the signaling theory was still relevant in influencing the movement of the share price.…”
Section: Dividend Signaling Theorymentioning
confidence: 99%